2016
DOI: 10.3390/ijerph13111123
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control in Smokers with Arterial Hypertension Who Switched to Electronic Cigarettes

Abstract: Electronic cigarettes (ECs) are battery-operated devices designed to vaporise nicotine, which may help smokers with quitting or reducing their tobacco consumption. No data is available regarding the health effects of ECs use among smokers with arterial hypertension and whether regular use results in blood pressure (BP) changes. We investigated long-term changes in resting BP and level of BP control in hypertensive smokers who quit or reduced substantially their tobacco consumption by switching to ECs. A medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
2
55
0
2
Order By: Relevance
“…Sixty‐seven remaining papers reported the impact of e‐cigarette use on abstinence from cigarettes or on the reduction in number of cigarettes consumed . Of these, six were from five RCTs , 19 were from longitudinal observational studies with a comparison group , two were from clinical laboratory studies , 15 were from longitudinal observational studies without a comparison group , 24 were from cross‐sectional surveys and one was a case–series .…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐seven remaining papers reported the impact of e‐cigarette use on abstinence from cigarettes or on the reduction in number of cigarettes consumed . Of these, six were from five RCTs , 19 were from longitudinal observational studies with a comparison group , two were from clinical laboratory studies , 15 were from longitudinal observational studies without a comparison group , 24 were from cross‐sectional surveys and one was a case–series .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the effects of e-cig on BP are limited. One study examined BP in smokers with arterial hypertension who switched to e-cig and found that patients who switched from tobacco smoking to e-cig had reduced resting BP and better BP control (113). This study suggests that e-cig may be less harmful than conventional cigarettes in hypertensive smokers but does not prove that e-cig has no adverse health consequences.…”
Section: Nicotine and The Ras In Cardiovascular Dysfunctionmentioning
confidence: 92%
“…Similarly, a marked attenuation in CS consumption was found in asthma patients who switched to E‐cigarettes, with better asthma control, lung function and lower airway hyper‐responsiveness over a 2‐year period . Regular E‐cigarette use could help reduce CS consumption in arterial hypertensive patients, further showing good blood pressure control and disease severity after 12 months' follow‐up …”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 94%
“…22 Regular E-cigarette use could help reduce CS consumption in arterial hypertensive patients, further showing good blood pressure control and disease severity after 12 months' follow-up. 23…”
Section: Benefits Of E-cigarette Usementioning
confidence: 99%